Comparative Effects of Phytoestrogen-Containing Preparations of the Kovrak (Ferula L.) Plant on the Clinical Indicators of Laying Hens - J.Sh. Ortikov; H.B. Niyazov; Sh.A. Pardaeva (American Journal of Biology and Natural Sciences, 2025)
This study investigates the effects of phytoestrogen-containing preparations derived from the Ferula (Kovrak) plant—namely “Panarut-98”, “Pano-25”, “Cufestrol”, and dried juice powder of F. kuhistanica—on the clinical indicators of laying hens when added to feed at a ratio of 10 g per 1000 kg for 60 days. The results demonstrated improvements in feed intake, vitality, and general condition of the hens, characterized by clean, moist, pink mucous membranes, shiny and smooth plumage, and bright red combs and wattles. Compared with the control group, full egg production was achieved earlier by 22 days with “Pano-25”, 18 days with “Panarut-98”, 15 days with F. kuhistanica juice powder, and 10 days with “Cufestrol”.